Plasmon-enhanced visible photodetectors based on hexagonal boron nitride (hBN) with gold (Au), silver (Ag), and non-alloyed bimetallic (Au/Ag) nanoparticles - Muhammad Nur Syafiq Mohamad Ismail; Muhammad Aiman Saufi Ahmad Fahri; Chee Leong Tan; Rozalina Zakaria (Scientific Reports)
Abstract Two-dimensional (2D) hexagonal boron nitride (hBN) has garnered significant attention due to its exceptional thermal and chemical stability, excellent dielectric properties, and unique optical characteristics, making it widely used in deep ultraviolet (DUV) applications. However, the integration of hBN with plasmonic materials in the visible region (532 nm) has not been fully explored, particularly in terms of morphology regulation and size control of mono- and bimetallic nanoparticles (BMNPs) namely gold (Au), silver (Ag) and Au-Ag. A Schottky junction-based metal–semiconductor contact configuration is employed to achieve hot-carrier reflections on the metal side, enhancing the quantum efficiency of the photodetector. The fabricated metallic NPs/hBN photodetector demonstrates a responsivity of 1.33 A/W, a specific detectivity of 1.03 × 1011 Jones, an ultra-low dark current of 7.00 µA and a high photo response ratio of 2.47. This improved performance is attributed to the visible light-modulated band-to-band excitation in hBN layer and internal photoemission resulting from the NPs/hBN junction. The device also exhibits a rapid response speed of less than 300 µs for all the devices. This approach of integrating 2D/metal opens possibilities for fabricating low-cost, high-performance, flexible photodetectors for a range of optoelectronic devices.